PENGARUH BRAND IMAGE, HARGA, VARIASI PRODUK, DAN BRAND AMBASSADOR GISELLA ANASTASIA TERHADAP KEPUTUSAN PEMBELIAN PRODUK MADAME GIE - Pramudita Kusuma Wardani, Dhias; Eni Kusrini (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2023)
This study aims to determine the effect of brand image, price, product variety, brand ambassador Gisella Anastasia on purchasing decisions for Madame Gie products. This study uses a quantitative approach. The data analysis technique uses multiple linear regression using SPSS version 16. The population of this study is Madame Gie's customers. The research sample involved 110 Madame Gie customer respondents in the Kudus Regency area. With data collection techniques using a questionnaire / questionnaire. With the result that brand image and price show that there is a significant and positive influence on purchasing decisions. Meanwhile, product variations and brand ambassadors did not have a significant and positive effect on purchasing decisions for Madame Gie's products.